MINAT BELAJAR DAN HASIL BELAJAR SISWA KELAS V DENGAN PEMBELAJARAN BERBANTUAN POWER POINT - Alexsandra Marius; Nelly Wedyawati; Melinda Rismawati (JUTECH : Journal Education and Technology, 2020)
ABSTRACTThis action research is held out due to the student's low interest in learning and low learning outcomes in science subjects for fifth grade students at SDN 11 Nyanggai. This research is intended to describe the application of powerpoint media in increasing learning interest and learning outcomes of the students; To describe the activity of learning interest and student's learning outcomes with powerpoint media; To describe the Increasement of student's interest in learning and learning outcomes using powerpoint media in the class. The research method that used is qualitative in the form of Classroom Action Research (CAR). The research subjects are Class V students of SDN 11 Nyanggai, with total of 15 people. Data collection tools that used in this research were observation sheets, and interview tests. Data analysis that used are quantitative analysis techniques for test results, and qualitative for non-test results. The calculation results of the observation sheet were categorized very well, as it seen from the results of the calculation from teacher's observation sheet on the first cycle which is obtained 100% results; the calculation of student's observation sheet on cycle I is 86.67%; the results of the teacher's observation sheet on ctcle II is obtained 100% results; the calculation of student's observation sheet on cycle II is obtained 100% results, there is an increasing of 13.33%. While the test results are categorized very well, which is the results of student's learning completeness on first cycle is 66.66% and in the second cycle is increasing to 93.33%,tehrefore there is an increasement from the first cycle to the second cycle of 26.67%. Thus, it shows that the powerpoint media can be an effective learning media to increase student's learning interest and learning outcomes. This research is recommended for teachers, students, schools, and further research on the implementation of powerpoint media on natural science subjects of class V students.Keywords: Learning Interest Increasement, Learning Outcomes, Powerpoint MediaABSTRAKPenelitian tindakan dilakukan karena rendahnya minat belajar dan hasil belajar siswa pada mata pelajaran IPA kelas V SDN 11 Nyanggai. Penelitian bertujuan untuk mendeskripsikan penerapan media powerpoint dalam meningkatan minat belajar dan hasil belajar bagi siswa. Metode penelitian adalah kualitatif dengan bentuk Penelitian Tindakan Kelas (PTK) sebanyak 2 siklus. Subyek penelitian siswa kelas V berjumlah 15 orang. Teknik pengumpul data adalah teknik observasi lansung teknik komunikasi lansung atau wawancara teknik dokumentasi. Alat pengumpul data dalam penelitian ini adalah lembar observasi lembar tes lembar wawancara Volume 1, Nomor 1, Juni 2020 28 dokumentasi. Analisis data menggunakan teknik analisis kuantitatif untuk hasil tes, dan kualitatif untuk hasil nontes. Hasil perhitungan lembar observasi dikategorikan sangat baik terlihat dari hasil perhitungan lembar observasi guru siklus I diperoleh hasil 100%; perhitungan lembar observasi siswa siklus I 86,67%; hasil perhitungan lembar observasi siklus II diperoleh hasil 100%; perhitungan lembar observasi siswa siklus II diperoleh hasil 100% sehingga terjadi peningkatan sebesar 13,33%. Sedangkan hasil tes dikategorikan sangat baik yaitu pada hasil siklus 1 ketuntasan belajar siswa adalah 66,66% dan pada siklus II mengalami peningkatan menjadi menjadi 93,33% sehingga terjadi peningkatan dari siklus I kesiklus II sebesar 26,67%. Hal ini menunjukkan bahwa media powerpoint mampu menjadi sebuah media pembelajaran yang efektif untuk meningkatkan minat belajar dan hasil belajar siswa. Penelitian ini disarankan bagi guru, siswa, sekolah dan penelitian selanjutnya dalam penggunaan media powerpoint pada mata pelajaran IPA siswa kelas V. Kata Kunci: Meningkatkan, Minat, Media, Belajar, Powerpoint